The Effectiveness of a Self-Determination Psychoeducational Program for Student with Intellectual Disability - Vilia Azhar Chinta Primadani; Pratiwi Widyasari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Intellectual disability is characterized by a deficit within an individual's intellectual and adaptive abilities. Young adults (18-25 years old) with intellectual disability are hampered in managing executive functions, such as planning, goal setting, or problem-solving abilities, which might hinder their life functioning during the transition to adulthood and post-school. There is a need for training on abilities which can facilitate individuals within this transition period, one of which is the ability of self-determination. This research aims to see the effectiveness of SDLMI (Self-Determined Learning Model of Instruction) program toward self-determination skills of an 18-year-old individual with intellectual disability. The method applied is a single subject pre-post test design, measured using knowledge evaluation and SDI:SR (Self-Determination Inventory: Students' Report). The results showed an increase in the subject's understanding and belief in their self-determination abilities. Apart from that, the subject was able to set goals and plan to achieve those goals. Even so, the subject still needed assistance in implementing the plans that have been prepared. This study implies the importance to practice self determination abilities for individuals with intellectual disability, accompanied by a structured collaboration and guidance from educational institutions and family.Disabilitas intelektual ditandai dengan adanya defisit pada kemampuan intelektual dan adaptif pada individu. Penyandang disabilitas intelektual yang berusia dewasa muda (18-25 tahun) terkendala dalam pengelolaan fungsi eksekutif yang melibatkan kemampuan perencanaan, penetapan tujuan, ataupun pemecahan masalah, dimana, hal ini dapat menghambat keberfungsian hidup mereka pada masa transisi menuju fase dewasa dan pasca sekolah. Diperlukan adanya pelatihan pada kemampuan yang dapat memfasilitasi individu dalam masa transisi tersebut, salah satunya adalah kemampuan determinasi diri. Penelitian ini bertujuan untuk melihat efektivitas program SDLMI (Self-Determined Learning Model of Instruction) terhadap kemampuan determinasi diri penyandang disabilitas intelektual berusia 18 tahun. Adapun metode yang digunakan adalah desain subjek tunggal pre-post test dengan pengukuran evaluasi pengetahuan dan SDI:SR (Self-Determination Inventory: Students' Report). Hasil penelitian menunjukkan adanya peningkatan dalam pemahaman serta keyakinan subjek terhadap kemampuan determinasi diri. Selain itu, subjek mampu untuk menetapkan tujuan serta melakukan perencanaan untuk mencapai tujuan tersebut. Meskipun begitu, subjek masih memerlukan adanya pendampingan dalam menerapkan perencanaan yang telah disusun. Adapun implikasi dari penelitian ini adalah untuk melatih kemampuan determinasi diri individu penyandang disabilitas intelektual, yang disertai dengan adanya kolaborasi dan bimbingan terstruktur dari institusi pendidikan dan keluarga.